Ganymede crater dimensions – Implications for central peak and central pit formation and development - Bray,VJ; Schenk,PM; Melosh,HJ; Morgan,JV; Collins,GS (Icarus, 2012)
The morphology of impact craters on the icy Galilean satellites differs from craters on rocky bodies. Thedifferences are thought due to the relative weakness of ice and the possible presence of sub-surface waterlayers. Digital elevation models constructed from Galileo images were used to measure a range of dimensionsof craters on the dark and bright terrains of Ganymede. Measurements were made from multipleprofiles across each crater, so that natural variation in crater dimensions could be assessed and averagedscaling trends constructed. The additional depth, slope and volume information reported in this work hasenabled study of central peak formation and development, and allowed a quantitative assessment of thevarious theories for central pit formation. We note a possible difference in the size-morphology progressionbetween small craters on icy and silicate bodies, where central peaks occur in small craters beforethere is any slumping of the crater rim, which is the opposite to the observed sequence on the Moon. Conversely,our crater dimension analyses suggest that the size-morphology progression of large lunar cratersfrom central peak to peak-ring is mirrored on Ganymede, but that the peak-ring is subsequentlymodified to a central pit morphology. Pit formation may occur via the collapse of surface material intoa void left by the gradual release of impact-induced volatiles or the drainage of impact melt intosub-crater fractures.